On the semantics of pace adverbs - Volfová, Kateřina (2006)
The aim of my thesis is to analyze the two readings of one of the pace adverbs quickly in connection with selected verbs (denoting for example an activity, or describing a speech act). These two possible readings (clausal and manner) influence the semantics of the adverb quickly; and therefore I attempted to identify the rules affecting the perception of the meaning of quickly (namely the characterization of verbs and the position of the adverb in the sentence). I also examined the adverb gradually; discussing in what respect it may be included in pace adverbs, trying to find out the features they share, and applying these on the interpretation of pace adverbs (slowly). This thesis is based on the British National Corpus